2018
DOI: 10.1002/aocs.12080
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Seed Coat on Oxidative Stability and Antioxidant Activity of Apricot (Prunus armeniaca L.) Kernel Oil at Different Roasting Temperatures

Abstract: Apricot kernels were roasted at various temperatures (120-180 C) for 10 min and changes in the fattyacid profiles, oxidative stability, and antioxidant activity, as well as the total phenolic contents (TPC) of the oils and skin (seed coat), were monitored. Roasting has no obvious influence on profiles and contents of fatty acid, induction period (IP), browning index, TPC, and antioxidant activity (2,2-diphenyl-1-picrylhydrazyl (DPPH), 2,2-azinobis (3-ethylbenzothiazoline-6-sulfonic acid), (ABTS) and Oxygen Rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…Therefore, the TV had following order: BHT < LSSCE 600 mg kg −1 < LSSCE 400 mg kg −1 < LSSCE 200 mg kg −1 . These results are in agreement with those reported by Zhouet al [61].…”
Section: K232 and K270valuessupporting
confidence: 94%
“…Therefore, the TV had following order: BHT < LSSCE 600 mg kg −1 < LSSCE 400 mg kg −1 < LSSCE 200 mg kg −1 . These results are in agreement with those reported by Zhouet al [61].…”
Section: K232 and K270valuessupporting
confidence: 94%
“…reducing power obtained at a concentration of 0.5 mg/ml. 52 reported that oil extracted from roasted apricot kernels at 120 °C to 180 °C temperatures for 10 min showed improved oxidative stability and antioxidant activity due to the production and transference of alcohol-soluble phenolics into the oil. Data obtained from research done in Turkey also showed that total antioxidant capacity, total carotenoid and total phenolic contents were highest in most of wild apricot fruits 53 .…”
Section: Phytochemicals In P Armeniaca Seed Oilmentioning
confidence: 99%
“…Data obtained from research done in Turkey also showed that total antioxidant capacity, total carotenoid and total phenolic contents were highest in most of wild apricot fruits 53 . Different studies are also available which showed the antioxidant activity of seed and fruit of P. armeniac 8,22,36,49,52 .…”
Section: Phytochemicals In P Armeniaca Seed Oilmentioning
confidence: 99%